Nursing Clinical Assessment of Factors Associated with Depression in Older People with Type 2 Diabetes in Primary Care: A Cross-sectional Research - Mukai, Helena Ayako; dos Santos, Ezequiel Aparecido; de Carvalho Nunes, Hélio Rubens [UNESP]; Barbosa, Guilherme Correa [UNESP]; Bocchi, Silvia Cristina Mangini [UNESP] (Bentham Science Publishers, 2024)
Background: Brazil has one of the largest older populations and people with diabetes. Non-communicable diseases account for 10.2% of hospitalisations in older people due to causes sensitive to primary care. Objective: This study aims to evaluate the factors associated with depression in older people with type 2 diabetes in primary care, according to the clinical nursing judgment based on NANDA-I Taxonomy II. Methods: This is a cross-sectional study of 389 older people with type 2 diabetes in primary care in a municipality in the state of São Paulo, Brazil. A bivariate analysis was performed to associate sociodemographic and clinical exposure variables with the outcomes of the geriatric depression scale. Only those variables associated at the level of p < 0.20 level were entered into a multiple logistic regression model. Results: The study identified two predictive factors: adherence to medication “low to probable low” (p=0.01; OR = 2.07 [95% CI 1.18-3.63]) and probability of repeat hospitalisations (Prh) (p<0.01; OR = 2.68 [95% CI: 1.42-5.04]). Therefore, it can be concluded that these factors are significant in predicting the outcome. Conclusion: Based on the interpretation of these factors, a cyclical procedural model has emerged that predicts and fosters depression in the population covered by primary care services, as well as signalling a risk for unstable blood glucose level and consequently a risk for metabolic syndrome and frail elderly syndrome. This is due to poor health in the community, which is related to programme failure and puts the group at risk.
Keywords: Aged; Cross-sectional studies; Depression; Diabetes mellitus; Frailty; Medication adherence; Nursing diagnosis; Primary care nursing